Alcohol use and dependence among the students attending ege university faculty of science - Yiğit, Şenay; Khorshid, Leyla (Journal of Dependence, 2006)
Objective: Alcohol use and dependence are some of the most important health problems among university students. This descriptive study was carried out to investigate alcohol use and dependence in this population. Method: The study sample consists of 300 students attending the Faculty of Science in Ege University. A questionnaire form and Michigan Alcoholism Screening Test were used in collecting the data. Data were analysed by using Chi-square test. Results: It was found that 76% of students were using alcohol, 8.8% of them had alcohol dependence and 14% had alcohol abuse. It was determined that the rate of alcohol dependence was significantly higher among students in 17-19 age group, and the rate of alcohol use was significantly lower among students who stayed in dormitory. Conclusion: Alcohol using and dependence is high in university students.